Indonesia Tanpa Jaringan Islam Liberal Follower’s Reception on the Anti-Sexual Violence Bill Content - Dwi Rizqa; Ichsan Adil Prayogi (Ikatan Sarjana Komunikasi Indonesia, 2024)
The democratic system in Indonesia supports the rise of anti-Western communities who reject the ideology of secularism, pluralism, and liberalism. Noted in several cases that occurred in Indonesia lately such as the 2017 DKI Jakarta Governor election and the 2019 presidential election as a sign of the rise of Islamic conservatism. Various actions oppose the dominant ideologies such as secularism, pluralism, and liberalism, one of them was the presence of Indonesia Tanpa Jaringan Islam Liberal (ITJ). The existence of ITJ until now voiced its rejection of the ideology of secularism, pluralism, and liberalism especially on social media. However, with the diversity of ITJ audiences, each message's reception will be different. Audiences are not always passive just accepting every message received. Therefore, this study will look at how acceptance of ITJ account followers on ITJ content using Stuart Hall's (1980) encoding-decoding theory. This study uses the constructivist paradigm and the methodology of transcendental phenomenology to understand the audience's experience in receiving content of ITJ and ideologies of secularism, pluralism, and liberalism. This research found various features of ITJ account followers in receiving the message displayed by ITJ. This study found that most informants understood and believed that Islamic religious values ​​can be a good solution for the system government. Truly the majority of Informants are in a negotiating position. The audience does not take the dominant ideology (secularism, pluralism, liberalism, or even conservative) for granted. There is an active role of the ITJ audience in receiving information.